Strategi Pemerintah dalam mencegah paham Radikalisme Di Era Penggunaan Media social di kalangan remaja - Maksin, Mastina Tina (Universitas PGRI Sumatera Barat, 2022)
Radicalism is an ideology or flow that wants social and political change or renewal by violent or drastic means, this is carried out by radical groups which justify various ways of carrying out their actions even though they take many victims, by justifying the teachings adhered to by these groups. As well as the radicalism network spreading various forms of propaganda to openly recruiting group members through social media or the internet, so that this becomes a problem where based on BPS data the population in Indonesia is dominated by productive groups, namely young people who are included in the category of Millennials and Generations